Florida [large type] - Groff, Lauren (Random House Large Print, 2018)
Florida: a place of storms, snakes, and sinkholes, and so much more. Lauren Groff explores a different side of her adopted home state in this collection of stories. The stories in this collection span characters, towns, decades, even centuries. Yet Florida-- its landscapes, climate, history, and state of mind-- becomes the gravitational center as Groff writes about loneliness, rage, family, and the passage of time.